Analgesic benefits of single-shot versus continuous adductor canal block for total knee arthroplasty: a systemic review and meta-analysis of randomized trials. Issue 2 (8th November 2022) - Hussain, Nasir; Brull, Richard; Zhou, Steven; Schroell, Robert; McCartney, Colin; Sawyer, Tamara; Abdallah, Faraj
Abstract : Background: Adductor canal block (ACB) can provide important analgesic benefits following total knee arthroplasty (TKA), however, the extent to which these benefits can be enhanced or prolonged by a continuous catheter-based infusion compared with a single-shot injection of local anesthetic is unclear. Objectives: This systematic review and meta-analysis (PROSPERO: CRD42021292738) review sought to compare the analgesic effectiveness of single shot to continuous ACB following TKA. Evidence review: We sought randomized trials from the US National Library of Medicine database (MEDLINE), Excerpta Medica database (EMBASE), and Cochrane Database of Systematic Reviews from inception to November 1, 2021, that compared single-shot to continuous ACB in adult patients undergoing TKA. The primary outcomes were (1) area under the curve (AUC) pain severity at rest and (2) cumulative opioid (oral morphine equivalent) consumption during the first 48 hours postoperatively. Secondary outcomes included postoperative pain severity scores up to 48 hours, cumulative opioid consumption at 24 hours, functional recovery, opioid-related side effects, and block-related complications. Risk of bias of included studies was assessed using the Cochrane risk of bias tool. Statistical pooling was conducted using the Hartung-Knapp-Sidik-Jonkman method for random effects. No funding was obtained for this review. Findings: Eleven trials (1185 patients) were included. No differences were observed in rest pain severity (AUC) or cumulative opioid consumption up to 48 hours postoperatively. In addition, no differences were observed in individual postoperative rest pain scores in the recovery room and at 12 and 24 hours, or in cumulative opioid consumption at 24 hours, functional recovery, and opioid-related side effects. Finally, fewer block-related complications were observed with single-shot ACB, with an OR (95% CI) of 0.24 (0.14 to 0.41) (p=0.002). Conclusions: Our results suggest that continuous catheter-based ACB does not enhance or prolong the analgesic benefits when compared with single-shot ACB for TKA over the first 48 hours postoperatively. Overall, the results of our meta-analysis do not support the routine use of continuous ACB for postoperative analgesia after TKA.